Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran IPS di SDN Tondo - Eka eviyanti123; herlina; arif firmansya; muchdar (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
This study aimed to determine the effect of using interactive learning media on the learning outcomes of fourth-grade students in Social Studies (IPS) at SDN Tondo. The population consisted of all 56 fourth-grade students, with Class IV A (28 students) as the control group and Class IV B (28 students) as the experimental group. This research applied a descriptive quantitative method, using observation, tests, and documentation as instruments. Data were collected through a posttest and analyzed using an independent sample t-test at a 5% significance level (α = 0.05). The results showed that the average score of the experimental class was 86.43, which was higher than the control class average of 64.29. Statistical analysis indicated a t-value of 7.653, while the t-table value was 2.005. Since t-value > t-table, the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that the use of interactive learning media had a significant positive effect on the Social Studies learning outcomes of fourth-grade students at SDN Tondo.